2003
DOI: 10.1037/1064-1297.11.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and rapid discounting of delayed hypothetical rewards in cocaine-dependent individuals.

Abstract: In this study, crack/cocaine-dependent (CD) and non-drug-using matched control (MC) participants were presented with hypothetical immediate and delayed rewards, with 16 delay conditions ranging from 5 min to 25 years. All participants were presented with hypothetical monetary rewards; however, the CD group was also presented with hypothetical crack/cocaine rewards. The objective value of the rewards ranged from $1 to $1,000. Hyperbolic discounting functions provided a good fit of the data. The CD group discoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
393
4
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(443 citation statements)
references
References 40 publications
(78 reference statements)
36
393
4
8
Order By: Relevance
“…In studies using hypothetical rewards, Odum, Madden, Badger, and Bickel (2000) also reported that people addicted to heroin discounted delayed heroin more steeply than delayed money, and Coffey, Gudleski, Saladin, and Brady (2003) reported that individuals dependent on crack/ cocaine discounted delayed cocaine rewards more steeply than they discounted hypothetical monetary rewards. Giordano et al (2002) replicated the finding that hypothetical heroin rewards were discounted more steeply than money by opioid-dependent individuals and also found that mild opiate deprivation increased the degree to which they discounted both types of reward.…”
Section: Applications To Group Differencesmentioning
confidence: 99%
“…In studies using hypothetical rewards, Odum, Madden, Badger, and Bickel (2000) also reported that people addicted to heroin discounted delayed heroin more steeply than delayed money, and Coffey, Gudleski, Saladin, and Brady (2003) reported that individuals dependent on crack/ cocaine discounted delayed cocaine rewards more steeply than they discounted hypothetical monetary rewards. Giordano et al (2002) replicated the finding that hypothetical heroin rewards were discounted more steeply than money by opioid-dependent individuals and also found that mild opiate deprivation increased the degree to which they discounted both types of reward.…”
Section: Applications To Group Differencesmentioning
confidence: 99%
“…Changes in time preferences could plausibly 25 mediate this pathway as individuals become more present-biased when stressed (Haushofer et al, 2015) and higher rates of intertemporal discounting are associated with cigarette smoking (Adams, 2009), frequent alcohol consumption (MacKillop and Kahler, 2009), illicit drug use (Coffey et al, 2003), lack of physical exercise (Leonard et al, 2013) and health outcomes such as obesity (Ikeda et al, 2016) and mortality (Boyle et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects who consistently choose the smaller immediate reinforcer are said to discount the value of the delayed reinforcer, and it is possible that drug abuse may occur, at least in part, because the beneficial value of drug abstinence is discounted compared to the immediate effects of a drug [21,48]. Accordingly, compared to nonusers, delayed rewards are discounted to a greater extent in users of opioids [40,41,48], alcohol [89], cocaine [17,34,40], methamphetamine [37,56], and cigarettes [4,11,36,55,58,72, but see 47]. It is likely that the increased discounting in drug abusers compared with nonabusers arises from a combination of factors, including higher baseline levels of impulsivity in drug abusers, increases in impulsivity due to acute or chronic drug effects, and common genetic and environmental factors that predispose individuals to both drug abuse and impulsive choice.…”
Section: Introductionmentioning
confidence: 99%